2022
DOI: 10.3389/fnins.2022.855483
|View full text |Cite
|
Sign up to set email alerts
|

Altered Brain Function and Causal Connectivity Induced by Repetitive Transcranial Magnetic Stimulation Treatment for Major Depressive Disorder

Abstract: ObjectiveRepetitive transcranial magnetic stimulation (rTMS) can effectively improve depression symptoms in patients with major depressive disorder (MDD); however, its mechanism of action remains obscure. This study explored the neuralimaging mechanisms of rTMS in improving depression symptoms in patients with MDD.MethodsIn this study, MDD patients with first-episode, drug-naive (n = 29) and healthy controls (n = 33) were enrolled. Depression symptoms before and after rTMS treatment were assessed using the Ham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Studies have shown that cognitive behavioral therapy aims to regulate emotions mainly by enhancing prefrontal function [ 44 ]. Another study showed that the function and metabolism of the middle frontal gyrus were significantly higher in MDD patients after antidepressant treatment, suggesting that the increased ReHo of the middle frontal gyrus may be an important marker of depression remission [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that cognitive behavioral therapy aims to regulate emotions mainly by enhancing prefrontal function [ 44 ]. Another study showed that the function and metabolism of the middle frontal gyrus were significantly higher in MDD patients after antidepressant treatment, suggesting that the increased ReHo of the middle frontal gyrus may be an important marker of depression remission [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The GCA method defines causal effects by examining whether the prior neural activity in one seed region predicts the activity in another region. GCA can be applied to time-series rs-fMRI data to identify the directional effective connectivity of functional interactions among brain regions ( Guan et al, 2022 ), and we employed it as such.…”
Section: Introductionmentioning
confidence: 99%
“… 23 Moreover, using voxel-based analyses, changes in brain activity in some regions implicated in the pathology of neurological and psychiatric disorders have been correlated with therapeutic effects. 24 , 25 However, few studies have employed voxel-based analysis to map the modulating effect of taVNS.…”
Section: Introductionmentioning
confidence: 99%